Method for optimizing apparent quality of fair-faced concrete by regulating WFT and PFT

By regulating the water-solid ratio (WFT) and slurry-solid ratio (PFT) of clean water concrete, a mathematical relationship model is established, and its apparent quality is optimized, which solves the problem of neglecting the composition of material components in the existing technology, and achieves an efficient and low-cost apparent quality improvement of clean water concrete.

CN119601139APending Publication Date: 2025-03-11CHINA CONSTR SCI & IND CORP LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411585545.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

When improving the apparent quality of clean water concrete, the prior art neglects the regulation of material components, resulting in increased engineering costs and poor results.

Method used

By measuring and calculating the performance parameters of raw materials, adjusting the water-solid ratio (WFT) and slurry-solid ratio (PFT), and establishing a mathematical relationship model with the surface quality parameters of clean water concrete, thereby optimizing and controlling the apparent quality of concrete.

Benefits of technology

It is achieved by regulating WFT and PFT to optimize the apparent quality of clean water concrete, reducing engineering costs, and improving the performance and appearance quality of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601139A_ABST
    Figure CN119601139A_ABST
Patent Text Reader

Abstract

The invention discloses a method for optimizing the apparent quality of fair-faced concrete by regulating WFT and PFT. The method comprises the following steps: 1) measuring and calculating performance parameters of raw materials; (2) determining WFT and PFT; and 3) representing the apparent quality of the C40 bare concrete, and optimizing and regulating the apparent quality of the concrete by establishing a mathematical relationship model between WFT and PFT and the surface quality parameters of the bare concrete, such as pore distribution and gray values.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fault handling, in particular to a method for optimizing the apparent quality of plain concrete by regulating WFT and PFT. Background Art

[0002] The architectural community generally believes that fair-faced concrete demonstrates the most essential architectural aesthetics of buildings. Compared with ordinary concrete, its natural surface as a decorative surface not only reduces or eliminates the cost associated with additional decorative surfaces, but also has a high-quality appearance while meeting mechanical and durability requirements. It has been widely used in domestic and foreign buildings. Since there is no decorative covering protection, fair-faced concrete materials need to have good appearance quality, which requires that the appearance of fair-faced concrete components is flat and smooth, with few pores and small color difference.

[0003] At present, most methods for improving the appearance of plain concrete structures focus on using low-friction molds and using uniform and stable cementitious materials, but generally ignore how to effectively improve the appearance of plain concrete by adjusting the composition of material components. For example, the patent "A modified wood fiber membrane for improving the appearance quality of plain concrete and its application" (patent number: 201010115134.X) discloses a modified wood fiber membrane for improving the appearance quality of plain concrete and its application, and proposes a method for improving the appearance quality of concrete by reducing the adhesion between the mold and the concrete surface and reducing the amount of bubbles on the concrete surface, but still does not consider how to optimize the appearance quality from the perspective of material composition. Instead, the introduction of new materials has increased the project cost. Patent "A method for preparing high-workability concrete using the thickness of the slurry film layer and the thickness of the water film layer"

[0004] (202410221470.4) Although a method of improving the working performance of concrete by regulating the thickness of the slurry layer and the thickness of the water film layer was proposed, it did not propose how to use the thickness of the slurry layer and the thickness of the water film layer to optimize the apparent quality of concrete.

[0005] The control of raw material components is a key factor affecting the appearance quality of formed plain concrete components. Therefore, the present invention proposes a method for optimizing the appearance quality of plain concrete by controlling WFT and PFT from the perspective of how to control and optimize the parameters of plain concrete raw materials to prepare plain concrete with excellent performance and good appearance quality. Summary of the invention

[0006] In view of the problems existing in the prior art, the object of the present invention is to provide a method for optimizing the surface quality of plain concrete by regulating WFT and PFT.

[0007] To solve the above problems, the present invention adopts the following technical solutions.

[0008] A method for optimizing the apparent quality of plain concrete by regulating WFT and PFT, comprising the following steps:

[0009] 1) Determine and calculate raw material performance parameters;

[0010] 2) Determination of WFT and PFT;

[0011] 3) Characterize the apparent quality of C40 plain concrete.

[0012] In step 1), the raw material performance parameters are determined and calculated as follows: The test process of expansion and T500 is carried out in accordance with GB / T 50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures". Each data is measured 6 times in total. After removing the maximum and minimum values, the average value of the remaining data is taken as the final value.

[0013] In step 2), the WFT and PFT are determined as follows: Through the wet stacking test, the maximum packing density φmax and the minimum void ratio umin (u = (1-φ) / φ) of the solid particles can be obtained, so that the WFT and PFT of each group of concrete can be calculated in combination with the test mix ratio. The calculation of WFT is shown in the following formulas (1)-(3):

[0014]

[0015] u' w =u w -u min (2)

[0016] A s =A C ×R C +A FA ×R FA +A SA ×R SA +A G ×R G +A SF ×R SF (3)

[0017] In the formula, u' w 、u w are respectively the water-richness ratio of concrete and the water-solid ratio in the actual concrete mix; A s A is the total specific surface area of ​​all solid particles in concrete; C , A FA , A SA , A G , A SF Corresponding to the specific surface areas of cement, fly ash, sand, stone, and stone powder respectively; R C , R FA , R SA, R G , R SF are the ratios of the volumes of cement, fly ash, sand, stone, and stone powder to the total volume of all solid particles in concrete;

[0018] The calculation process of PFT is as follows:

[0019]

[0020] u' p =u p -u Amin (5)

[0021] A A =A SA ×R SA +A G ×R G (6)

[0022] In the formula, u' p 、u p They are respectively the concrete slurry ratio and the slurry-solid ratio in the actual concrete mix (the volume ratio of slurry to the volume ratio of aggregate with a particle size greater than 0.075 mm); A A The total specific surface area of ​​all concrete aggregates with a particle size greater than 0.075 mm;

[0023] The specific surface area of ​​aggregate (particle size > 0.075 mm) can be calculated from the particle size distribution, as shown in the following formula (7):

[0024]

[0025] Where ρ is the apparent density of aggregate; mi and Di are the mass fraction and average particle size of aggregate of the ith particle size, respectively.

[0026] In step 3), the apparent quality of C40 plain concrete is characterized as follows: a plain wooden formwork is selected as the formwork for forming plain concrete specimens, and the specimen forming size is 300 mm × 300 mm × 50 mm. First, before casting the formed concrete specimens, it is necessary to ensure that the inside of the test mold and the inner surface of the formwork are not contaminated. After casting, the vibrator is vibrated for 10 seconds to ensure the compactness of the concrete. After the concrete casting is completed, the formwork is removed 24 hours after the concrete casting is completed, and the specimen is placed in a standard curing room for curing for 7 days. Subsequently, the formed and cured plain concrete specimens are placed under the same environment and lighting conditions, and the surface of the concrete specimens is photographed at the same vertical height using a camera. The image information of the photographed plain concrete specimens is gray-processed using Image J software to obtain the image grayscale histogram of the corresponding concrete specimen. At the same time, the grayscale standard deviation of the concrete image is calculated based on the grayscale value of the collected concrete image and the mean value of the image grayscale level, thereby reflecting the color difference of the collected specimen image and the discrete degree of the target data set, as shown in formula (8):

[0027]

[0028] Where Std is the grayscale standard deviation of the collected image; M is the total number of rows in the image; N is the total number of columns in the image; Gray(i,j) is the grayscale level of each pixel in the collected image; is the average grayscale level of the image. The smaller the grayscale standard deviation, the smaller the color difference of the image, indicating that the color of the concrete surface is more uniform.

[0029] Beneficial effects of the present invention

[0030] Compared with the prior art, the advantages of the present invention are:

[0031] The main content of the present invention is to propose a mathematical relationship model between WFT and PFT and surface quality parameters (pore distribution, gray value) of plain concrete, so as to optimize and regulate the apparent quality of concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a diagram showing the influence of different material component dosages on the working performance of fair-faced concrete.

[0033] Figure 2 This is a graph showing the variation of the strength of plain concrete under different material component dosages.

[0034] Figure 3 This is a graph of grayscale grade and grayscale standard deviation of plain concrete material at different material component dosages.

[0035] Figure 4 The WFT and PFT diagrams of bare concrete under different factors and variables.

[0036] Figure 5 This is the effect of WFT on the working performance of C40 plain concrete.

[0037] Figure 6 This is a diagram showing the influence of PFT on the working performance of C40 plain concrete.

[0038] Figure 7 This is the relationship diagram between the grayscale standard deviation of plain concrete and WFT and PFT.

[0039] Figure 8 This is the sample drawing of the trial mix of plain concrete at the construction site. DETAILED DESCRIPTION

[0040] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention; it is obvious that the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments, and all other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making creative work are within the scope of protection of the present invention.

[0041] 1.1 Raw materials

[0042] The P·O 42.5 ordinary Portland cement produced by Yingde Conch Company has a density of 3.02g / cm3 and a specific surface area (SSA) of 354.87m2 / kg; the F-type II fly ash produced by New Resources Building Materials Mawan Power Plant has a density of 2.32g / cm3 and a specific surface area of ​​340.7m2 / kg; the fine aggregate is washed sand with an apparent density of 2.6g / cm3, a fineness modulus of 2.6, and a particle grading of II zone. At the same time, the specific surface area of ​​particles <0.075mm in the sand is 124.94m2 / kg, and it is used as stone powder; the coarse aggregate is 5-16mm continuously graded basalt crushed stone with an apparent density of 2.6g / cm 3 The admixture is FST-6 polycarboxylic acid high-performance slow-setting water-reducing agent with a solid content of 10.18% (mass fraction) provided by Foshan Huaxuan New Materials Co., Ltd. The fiber is basalt fiber with a length of 12 mm and a diameter of 18 μm provided by Shenzhen Boste Engineering Materials Co., Ltd., with a density of 2.65 g / cm3, a specific surface area of ​​2.5×105 m2 / m3[16,17], a tensile strength of 2196 MPa, and an elastic modulus of 40.67 GPa.

[0043] 1.2 Mix ratio of plain concrete

[0044] According to JG / J 55-2011 "Ordinary Concrete Mix Design Code" and JGJ 169-2009 "Bare Face Concrete Application Technical Code", the experiment was designed based on the C40 bare face concrete mix design. According to the previous experimental research, the fly ash content of the bare face concrete was determined to be 20%, and the water reducer content was 1.8%. Combining the WFT and PFT theories, the influence of the three factors of water-binder ratio, sand ratio, and fiber dosage on the working performance, mechanical properties, and apparent properties of concrete was studied.

[0045] Table 1 Mixing proportion of fair-faced concrete

[0046]

[0047] The specific surface areas of aggregates of different particle sizes can be obtained by formula (7) as shown in Table 2.

[0048] Table 2 The particle size distribution characteristics and specific surface area of ​​the aggregate

[0049]

[0050] 2.2 Mechanical properties

[0051] like Figure 2As shown in the figure, with the increase of curing age, the strength of the plain concrete specimens increased significantly, and the 28d strength could reach more than 30MPa. As the water-cement ratio increased from 0.3 to 0.4, the compressive strength of the 28d plain concrete specimens decreased from 58.7MPa to 34.8MPa, and the flexural strength decreased from 4.17MPa to 2.84MPa. This is because the increase in the water-cement ratio increased the amount of water in the plain concrete material, increased the pores inside the concrete, and reduced the density and mechanical properties of the plain concrete specimens. With the change of sand ratio, the strength of the 3d plain concrete specimens was not significantly affected, and the strength of the 28d plain concrete specimens increased with the increase of sand ratio. Among them, when the sand ratio was 0.45, the compressive strength and splitting tensile strength of the 28d plain concrete material reached 64.8MPa and 4.27MPa, respectively. According to the closest packing theory, this may be due to the increase in sand ratio, which reduces the voids inside the plain concrete material, increases the density of the plain concrete material, and thus improves the strength of the plain concrete material. In addition, with the increase in the amount of basalt fiber, the strength of concrete shows a trend of first increasing and then decreasing. When the fiber content is 0.5%, the compressive strength of the plain concrete material at 28 days can reach 57MPa, and the splitting tensile strength can reach 4.1MPa. As the fiber content is further increased to 0.7%, the strength of the plain concrete sample is significantly reduced. This is because the excessively high amount of fiber is easy to agglomerate inside the concrete, which will aggravate the generation of cracks inside the plain concrete material.

[0052] 2.3 Apparent quality

[0053] Figure 3The grayscale distribution curve and grayscale standard deviation of the apparent image of the 28d plain concrete sample under different water-binder ratios, sand ratios, and fiber content. With the increase of the water-binder ratio, the grayscale distribution curve of the surface of the 28d plain concrete sample shifts toward the direction of smaller grayscale levels and the frequency peak gradually decreases. Among them, when the water-binder ratio is 0.4 (1# sample), the grayscale standard deviation of the surface of the plain concrete sample reaches 33.5. This shows that with the increase of the water-binder ratio, the surface of the plain concrete gradually turns black, and the color difference is obvious. This is because the working performance of the freshly mixed slurry of the plain concrete gradually improves with the increase of the water-binder ratio, and even the freshly mixed concrete slurry will show segregation, bleeding, and even yellowing slurry. At the same time, the unburned carbon or oil contained in the fly ash gradually accumulates and floats on the surface of the concrete slurry, resulting in significant differences in the apparent color of the plain concrete and a large grayscale standard deviation. In addition, with the increase of sand ratio and fiber content, the gray scale of the plain concrete has no obvious change difference, which is between 100-200, and the gray scale standard deviation of the plain concrete sample is below 15, indicating that the sand ratio and fiber content have little effect on the apparent quality of the plain concrete, because the change of sand ratio and fiber does not cause segregation and bleeding of the fresh plain concrete paste. This also further proves that the working performance of the fresh plain concrete paste is correlated with its apparent quality after hardening and molding.

[0054] 2.4 Bulk density, WFT and PFT

[0055] The packing density, water enrichment rate, WFT and PFT of the bare concrete materials were determined by wet packing test, as shown in Table 3 and Figure 4As shown. It can be seen that with the increase of water-binder ratio, since the solid particle component in the plain concrete does not change, the packing density remains at 0.8783, while the water-rich rate gradually increases, and the WFT and PFT of the plain concrete increase, which is directly caused by the increase in water consumption. When the sand ratio increases from 0.37 to 0.45, the packing density decreases from 0.8839 to 0.8701, the water-rich rate and SSA increase from 0.0888 and 229484.7m2 / m3 to 0.0708 and 231562.1m2 / m3, respectively, while the WFT and PFT decrease from 0.3871μm and 67.47μm to 0.3059μm and 62.14μm, respectively. This is because the increase in sand ratio increases the total specific surface area of ​​solid particles in the plain concrete, resulting in an increase in the total adsorbed water at the same water consumption, thereby reducing WFT and PFT[]. In addition, as the fiber content increases from 0.3% to 0.7%, the bulk density, water richness and SSA of the plain concrete paste increase from 0.8747, 0.0771, 230508.9m2 / m3 to 0.8825, 0.0869, 230526m2 / m3, respectively, and the calculated WFT and PFT increase from 0.3343μm and 63.29μm to 0.3771μm and 63.51μm, respectively. This is because the increase in fiber content not only increases the total amount of plain concrete materials and the total particle specific surface area, but also fills the gaps between aggregate particles due to the fiber, reducing the actual total specific surface area of ​​plain concrete, thereby increasing WFT and PFT.

[0056] Table 3 Packing density, WFT and PFT results of fair-faced concretes

[0057]

[0058] 2.5 Effect of WFT and PFT on Work Performance

[0059] By comparing the relationship between workability (spread, slump and inverted emptying) and WFT, such as Figure 5 As shown. It can be seen that different factors have different effects on the working performance and WFT of plain concrete paste. Among them, under the influence of water-cement ratio, the working performance gradually tends to be flat with the increase of WFT, until the expansion, slump and inverted emptying reach 610mm, 228mm and 4.69s respectively, which depends on the water demand of the paste. Under the influence of sand ratio, the expansion and slump decrease with the increase of WFT, while the inverted emptying remains the same. In addition, due to the influence of fiber content, the expansion and inverted emptying gradually decrease with the increase of WFT, while the slump increases. In addition, from Figure 6The relationship between work performance and PFT shows that under the influence of different factors, the change pattern of PFT is basically consistent with WFT.

[0060] 2.6 Effect of WFT and PFT on apparent quality

[0061] Figure 7 The relationship between WFT and PFT and the grayscale standard deviation of plain concrete is shown in Figure 2. It can be seen that under different influencing factors, the change patterns between WFT and PFT and the grayscale standard deviation are similar. Under the influence of water-cement ratio, with the increase of WFT and PFT, the grayscale standard deviation gradually increases. When WFT and PFT reach 0.4832μm and 70.82μm, respectively, the grayscale standard deviation reaches 34.5. With the change of WFT and PFT, under the influence of sand ratio and fiber, there is no significant difference in the grayscale standard deviation, indicating that the sand ratio and fiber have little effect on the apparent quality of plain concrete materials.

[0062] 2.7 Verify the prepared plain concrete

[0063] The above method shows that the apparent quality and working performance of plain concrete are mainly determined by the WFT and PFT of the concrete paste. When the WFT and PFT are in the range of 0.3-0.4μm and 60-65μm respectively, the plain concrete has good apparent quality and working performance. In order to verify the apparent quality of plain concrete under this paste parameter, mix 2# was selected for trial mixing and two parallel specimens were formed. Figure 8 It can be seen that between the adjusted WFT and PFT parameters, the surface of the prepared plain concrete specimens has no obvious pores and color difference.

[0064] The above is only a preferred specific implementation of the present invention; however, the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solution and its improved conception within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for optimizing the apparent quality of plain concrete by regulating WFT and PFT, characterized in that: The following steps are involved: 1) Determine and calculate raw material performance parameters; 2) Determination of WFT and PFT; 3) Characterize the apparent quality of C40 plain concrete.

2. The method for optimizing the apparent quality of plain concrete by regulating WFT and PFT according to claim 1, characterized in that: In step 1), the raw material performance parameters are determined and calculated as follows: The test process of expansion and T500 is carried out in accordance with GB / T50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures". Each data is measured a total of 6 times. After removing the maximum and minimum values, the average value of the remaining data is taken as the final value.

3. The method for optimizing the apparent quality of plain concrete by regulating WFT and PFT according to claim 2, characterized in that: In step 2), the WFT and PFT are determined as follows: Through the wet stacking test, the maximum packing density φmax and the minimum void ratio umin (u = (1-φ) / φ) of the solid particles can be obtained, so that the WFT and PFT of each group of concrete can be calculated in combination with the test mix ratio. The calculation of WFT is shown in the following formulas (1)-(3): in' w =in w -in min (2) A s =A C ×R C +A FA ×R FA +A SA ×R SA +A G ×R G +A SF ×R SF (3) In the formula, u' w 、u w are respectively the water-richness ratio of concrete and the water-solid ratio in the actual concrete mix; A s A is the total specific surface area of ​​all solid particles in concrete; C , A FA , A SA , A G , A SF Corresponding to the specific surface areas of cement, fly ash, sand, stone, and stone powder respectively; R C , R FA , R SA , R G , R SF are the ratios of the volumes of cement, fly ash, sand, stone, and stone powder to the total volume of all solid particles in concrete; The calculation process of PFT is as follows: in' p =in p -in Amin (5) A A =A SA ×R SA +A G ×R G (6) In the formula, u′ p 、u p They are respectively the concrete slurry ratio and the slurry-solid ratio in the actual concrete mix (the volume ratio of slurry to the volume ratio of aggregate with a particle size greater than 0.075 mm); A A The total specific surface area of ​​all concrete aggregates with a particle size greater than 0.075 mm; The specific surface area of ​​aggregate (particle size > 0.075 mm) can be calculated from the particle size distribution, as shown in the following formula (7): Where ρ is the apparent density of aggregate; mi and Di are the mass fraction and average particle size of aggregate of the ith particle size, respectively.

4. The method for optimizing the apparent quality of plain concrete by regulating WFT and PFT according to claim 1, characterized in that: In step 3), the apparent quality of C40 plain concrete is characterized as follows: a plain wooden formwork is selected as the formwork for forming plain concrete specimens, and the specimen forming size is 300 mm × 300 mm × 50 mm. First, before casting the formed concrete specimens, it is necessary to ensure that the inside of the test mold and the inner surface of the formwork are not contaminated. After casting, the vibrator is vibrated for 10 seconds to ensure the compactness of the concrete. After the concrete casting is completed, the formwork is removed 24 hours after the concrete casting is completed, and the specimen is placed in a standard curing room for curing for 7 days. Subsequently, the formed and cured plain concrete specimens are placed under the same environment and lighting conditions, and the surface of the concrete specimens is photographed at the same vertical height using a camera. The image information of the photographed plain concrete specimens is gray-processed using Image J software to obtain the image grayscale histogram of the corresponding concrete specimen. At the same time, the grayscale standard deviation of the concrete image is calculated based on the grayscale value of the collected concrete image and the mean value of the image grayscale level, thereby reflecting the color difference of the collected specimen image and the discrete degree of the target data set, as shown in formula (8): Where Std is the grayscale standard deviation of the collected image; M is the total number of rows in the image; N is the total number of columns in the image; Gray(i,j) is the grayscale level of each pixel in the collected image; is the average grayscale level of the image. The smaller the grayscale standard deviation, the smaller the color difference of the image, indicating that the color of the concrete surface is more uniform.

Citation Information

Patent Citations

  • Modified wood fiber membrane for improving surface quality of fair-faced concrete and application thereof

    CN101793090A

  • Method for preparing high-workability concrete by utilizing slurry film layer thickness and water film layer thickness

    CN118053524A